2017
DOI: 10.1080/21501203.2017.1394393
|View full text |Cite|
|
Sign up to set email alerts
|

Testing sampling effort and relative abundance descriptors of belowground ectomycorrhizal fungi in a UK planted scots pine woodland

Abstract: The native Caledonian pinewoods of Scotland, UK contain a unique and unexplored biodiversity of below-ground ectomycorrhizal fungi which may constitute a valuable source of microbial genetics resources for woodland restoration. In this study we test the sampling effort, taxa detection (ectomycorrhiza morpho-anatotyping) and relative abundance measurements (ectomycorrhizal root tip number vs. dry weight) of below-ground ectomycorrhizal fungal communities in a planted Pinus sylvestris Caledonian woodland. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Cortinarius is the largest genus of ectomycorrhizal fungi (> 2,000 species) ( Høiland and Holst-Jensen, 2000 ; Soop and Gasparini, 2011 ), and represents approximately 10% of the species forming ectomycorrhizae ( Rinaldi et al., 2008 ). Cortinarius species often dominate the ectomycorrhizosphere in reforested plots ( Stefani et al., 2009 ; Pickles et al., 2010 ; Villarreal-Ruiz and Neri-Luna, 2017 ; Haas et al., 2018 ). Their extraradical mycelium is classified as a medium-distance exploratory type ( Agerer, 2001 ; Agerer and Raidl, 2004 ), in the fringe subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Cortinarius is the largest genus of ectomycorrhizal fungi (> 2,000 species) ( Høiland and Holst-Jensen, 2000 ; Soop and Gasparini, 2011 ), and represents approximately 10% of the species forming ectomycorrhizae ( Rinaldi et al., 2008 ). Cortinarius species often dominate the ectomycorrhizosphere in reforested plots ( Stefani et al., 2009 ; Pickles et al., 2010 ; Villarreal-Ruiz and Neri-Luna, 2017 ; Haas et al., 2018 ). Their extraradical mycelium is classified as a medium-distance exploratory type ( Agerer, 2001 ; Agerer and Raidl, 2004 ), in the fringe subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that ectomycorrhizal fungi, wood-decaying fungi, soil saprotrophs, and litter saprotrophs were predominantly present in mixed forests ( Figure 4 b). Ectomycorrhizal fungi, such as Lactarius [ 46 , 47 ], Amanita [ 48 , 49 ], Russula [ 50 , 51 ], and Cortinarius [ 52 , 53 ], are known to associate primarily with Quercus and Pinus trees. Since mixed forests in our study area consist of Quercus mongolica and Pinus koraiensis , it is likely that the presence of these tree species contributes to the higher abundance of ectomycorrhizal fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…1). Roots were collected from a total of 18 soil samples, distributed as follows: (a) six samples at 20 cm intervals, (b) four samples at 1 m intervals, (c) four samples at 10 m intervals, and (d) four samples at 25 m intervals, according to the methodology described by Villarreal-Ruiz & Neri-Luna (2018). Soil samples were extracted as soil cores measuring 15 cm in length and 5 cm in diameter using a soil core sampler.…”
Section: Experimental Design and Sampling Methodsmentioning
confidence: 99%